CETRIFUGAL GENERATORS OF THE EXCITING FORCE OF VIBRATION-SEISMIC SOURCES OF OSCILLATIONS - Cherednikov E.N. (My University, 2001)
Operation of powerful vibration-seismic sources has been considered. They are used for excitation of seismic waves in geological medium. Application of two-axis four-shaft generator of oscillations for vibration-seismic sources has been ground basing on analysis of known designs of centrifugal vibrators. Two electric motors are used as drive for the generator. Scheme of the generator has been presented. Creation of the generator according to the given design-kinematic scheme makes it possible to provide vertical force which is constant for various frequencies and can be harmonically varied. Symmetric and uniform distribution of the force in the radiating platform is noted.